Aktivitas Penghambatan Enzim α-Glukosidase dari Ekstrak Hasil Fermentasi Bakteri Endofit dari Tapak Dara (Catharanthus roseus (L.) G. Don) Daun - Ulfa Rosiatul Huda; Friardi Ismed; Nurwahidatul Arifah; Valdy Filando Sardy; Rustini (Postgraduate, University of Mataram, 2024)
Catharanthus roseus (L.) G. Don contain bioactive compounds that act as inhibitors against the α-glucosidase enzyme. This study aims to test the α-glucosidase enzyme inhibitor activity of fermented extract of endophytic bacteria from tapak dara leaves and identify the bacterial species. Endophytic bacteria were isolated using a direct planting method, resulting in eight isolates. The bacteria were fermented for 24-72 hours in nutrient broth media. Ethyl acetate was used to extract the fermented bacteria. Screening for α-glucosidase enzyme inhibitory activity was conducted using the TLC bioautography method. Four bacterial isolates (TD 1, TD 3, TD 4, TD 7) produced clear zones, qualitatively indicating that the isolates have inhibitory activity against the α-glucosidase enzyme. The IC50 results from the eight isolates showed that three isolates provided strong IC50 values: isolate TD 1 at 19.93 µg/ml, isolate TD 2 at 92.34 µg/ml, and isolate TD 4 at 13.94 µg/ml, compared to acarbose at 48.85 µg/ml). Molecular identification showed that isolate TD 1 was Pseudomonas oryzihabitans and isolate TD 4 was Staphylococcus warneri. This study concluded that endophytic bacteria from tapak dara leaves have the potential as a source of α-glucosidase enzyme inhibitor compounds for the development of antidiabetic drugs.